Project LIFE PRIMED: Integrating interdisciplinary and ecosystem-based approaches in restoring endangered mediterranean coastal forests and freshwater ecosystems - V. E.Cambria; D. La Montagna; M. Beccaccioli; V. C. Cuccaro; F. M. De Filippi; G. Fabrini; G. Fanelli; F. Francesconi; C. Georgiadis; E. Korakaki; T. Merou; P. Michopoulos; et al. (Journal of Coastal Conservation, 2025)

The CRZ1 transcription factor in plant fungi: regulation mechanism and impact on pathogenesis - A. Cacciotti; M. Beccaccioli; M. Reverberi (Molecular Biology Reports, 2024)
Calcium (Ca 2+ ) is a universal signaling molecule that is tightly regulated, and a fleeting elevation in cytosolic concentration triggers a signal cascade within the cell, which is crucial for several processes such as growth, tolerance to stress conditions, and virulence in fungi. The link between calcium and calcium-dependent gene regulation in cells relies on the transcription factor Calcineurin-Responsive Zinc finger 1 (CRZ1). The direct regulation of approximately 300 genes in different stress pathways makes it a hot topic in host-pathogen interactions. Notably, CRZ1 can modulate several pathways and orchestrate cellular responses to different types of environmental insults such as osmotic stress, oxidative stress, and membrane disruptors. It is our belief that CRZ1 provides the means for tightly modulating and synchronizing several pathways allowing pathogenic fungi to install into the apoplast and eventually penetrate plant cells (i.e., ROS, antimicrobials, and quick pH variation). This review discusses the structure, function, regulation of CRZ1 in fungal physiology and its role in plant pathogen virulence.

More nature in the city - G Capotorti; S Bonacquisti; L Abis; I Aloisi; F Attorre; G Bacaro; G Balletto; E Banfi; E Barni; F Bartoli; E Bazzato; M Beccaccioli; et al. (Plant Biosystems, 2020)